2018
DOI: 10.1093/scan/nsy011
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and neural indices of affective coloring for neutral social stimuli

Abstract: Emotional processing often continues beyond the presentation of emotionally evocative stimuli, which can result in affective biasing or coloring of subsequently encountered events. Here, we describe neural correlates of affective coloring and examine how individual differences in affective style impact the magnitude of affective coloring. We conducted functional magnetic resonance imaging in 117 adults who passively viewed negative, neutral and positive pictures presented 2 s prior to neutral faces. Brain resp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 68 publications
2
14
0
Order By: Relevance
“…Prior research has demonstrated that ratings of novel neutral as well as emotionally ambiguous faces are influenced by emotional state, by priming with affective images, and by dispositional characteristics in a phenomenon described as affective bias or coloring [33, 34]. Here, novel neutral African American, White, and Asian female and male faces appeared on a computer screen with a visual slider underneath ranging from 0 (not at all likable) to 100 (very likable).…”
Section: Methodsmentioning
confidence: 99%
“…Prior research has demonstrated that ratings of novel neutral as well as emotionally ambiguous faces are influenced by emotional state, by priming with affective images, and by dispositional characteristics in a phenomenon described as affective bias or coloring [33, 34]. Here, novel neutral African American, White, and Asian female and male faces appeared on a computer screen with a visual slider underneath ranging from 0 (not at all likable) to 100 (very likable).…”
Section: Methodsmentioning
confidence: 99%
“…Individual differences in amygdala response to fearful faces predict how negatively a subsequent, unrelated neutral stimulus is appraised (Lapate et al, 2016;Lapate et al, 2017). This biasing effect may be due to persistence of amygdala activity following emotionally evocative stimuli that 'spills over' into the encoding of the subsequent neutral stimulus (Grupe et al, 2018;Tambini et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have similarly demonstrated that acute stress alters how facial emotions are processed in healthy individuals (Chen et al 2014 ; Daudelin-Peltier et al 2017 ). Recently, Grupe et al ( 2018 ) demonstrated that neural responses to neutral facial stimuli were differentially modulated based on the valence (negative or positive) of the faces presented immediately prior, with greater amygdalar activations for neutral faces that were presented after negative faces. Considering our results in light of this literature, we surmise that evaluating previously seen information in an altered emotional state, i.e., under stress, may have transformed the previously neutral stimuli into more emotionally salient, resulting in the observed change in threat ratings for neutral faces.…”
Section: Discussionmentioning
confidence: 99%